Menguatkan Pendidikan Keuangan berbasis Islam: Analisis Pengaruh Environmental Social and Governance (ESG) terhadap Kinerja Saham dalam Pendidikan Keuangan - Nurheni, Siska; Nurfitri, Serlina; Kusumah, Dewita Febriyanti (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) on the stock performance of PT Unilever Indonesia Tbk during the period 2013–2023. The research uses a quantitative approach with a simple linear regression method and secondary data collected from annual reports, sustainability reports, and market data. Stock performance is proxied by Tobin’s Q as an indicator of firm value. The results indicate that ESG has a negative but statistically insignificant effect on Tobin’s Q. The R-squared value of 0.0730 shows that ESG explains only a small portion of the variation in firm value. These findings suggest that ESG practices have not yet been fully perceived by the market as a decisive factor in determining firm value. This study contributes to sustainable finance literature and provides implications for companies, investors, and regulators in strengthening ESG implementation and communication strategies